The Affection Towards Animals in The Perspective of Hadith (Thematic Study) - Prayogi, Ananda (Green Publisher Indonesia, 2023)
The feeling of affection towards animals is now starting to disappear in most humans, especially Muslims. In fact, this feeling is something that was practiced by Rasulullah SAW. Of course, this raises a discrepancy between reality and the theory that should be done. This discrepancy raises the need for a more in-depth study in order to obtain a thorough understanding so that it can be realized more specifically by people who embrace Islam. This study uses library research methods with a qualitative approach. The data source is the hadith in kitub at-tis’ah as the main source for references in tracking hadith. The results of the research show that the existence of hadiths about compassion are quite numerous and valid. From here, practicing affection feeling for animals is indeed a good thing as exemplified by the Prophet Muhammad SAW as contained in a number of hadiths. Therefore, Islam considers acts of affection for animals as something which is recommended to be done.